Radical Reactions Affecting Polar Groups in Threonine Peptide Ions - Nguyen, Huong T H; Andrikopoulos, Prokopis C; Bím, Daniel; Rulíšek, Lubomír; Dang, Andy; Tureček, František (The journal of physical chemistry. B, 2017)
Peptide cation-radicals containing the threonine residue undergo radical-induced dissociations upon collisional activation and photon absorption in the 210-400 nm range. Peptide cation-radicals containing a radical defect at the N-terminal residue, [•Ala-Thr-Ala-Arg+H]+, were generated by electron transfer dissociation (ETD) of peptide dications and characterized by UV-vis photodissociation action spectroscopy combined with time-dependent density functional theory (TD-DFT) calculations of absorption spectra, including thermal vibronic band broadening. The action spectrum of [•Ala-Thr-Ala-Arg+H]+ ions was indicative of the canonical structure of an N-terminally deaminated radical whereas isomeric structures differing in the position of the radical defect and amide bond geometry were excluded. This indicated that exothermic electron transfer to threonine peptide ions did not induce radical isomerizations in the fragment cation-radicals. Several isomeric structures, ion-molecule complexes, and transition states for isomerizations and dissociations were generated and analyzed by DFT and Møller-Plesset perturbational ab initio calculations to aid interpretation of the major dissociations by loss of water, hydroxyl radical, C3H6NO•, C3H7NO, and backbone cleavages. Born-Oppenheimer molecular dynamics (BOMD) in combination with DFT gradient geometry optimizations and intrinsic reaction coordinate analysis were used to search for low-energy cation-radical conformers and transition states. BOMD was also employed to analyze the reaction trajectory for loss of water from ion-molecule complexes.
Keywords: časové faktory; Free Radicals; Threonine; volné radikály; threonin; Peptides; kationty; Cations; Time Factors; kvantová teorie; peptidy; Quantum Theory